A New Decomposition-Based Pricing Technique For Solving Large-Scale Mixed IP with a Computer Technique - Islam, A; Hasan, M Babul; Das, HK (GANIT: Journal of Bangladesh Mathematical Society, 2016)
In this paper, we develop a new Decomposition-Based Pricing (DBP) procedure to filter the unnecessary decision ingredients from large scale mixed integer programming (MIP) problem, where the variables are in huge number will be abated and the complicacy of restrictions will be straightforward. We then develop a generalized computer technique corresponding to our new DBP method by using the programming language A Mathematical Programming Language (AMPL). A number of examples have been illustrated to demonstrate our method. GANIT J. Bangladesh Math. Soc.Vol. 34 (2014) 5-20